Canine leptospirosis in Canada, test-positive proportion and risk factors (2009 to 2018): A cross-sectional study - Stull, Jason W.; Evason, Michelle; Weese, J. Scott; Yu, Jenny; Szlosek, Donald; Smith, Amanda M. (PLOS ONE, 2022)
Over the past decade, there has been an apparent increased frequency and widened distribution of canine leptospirosis in Canada, however, this has been minimally investigated. Availability and clinical uptake of Leptospira polymerase chain reaction (PCR)-based testing of dogs in Canada may provide important insight into the epidemiology of this canine and zoonotic infectious disease. Study objectives were to evaluate clinical canine Leptospira PCR test results from a large commercial laboratory to determine temporal and spatial distribution in Canada and identify dog, geographic and temporal risk factors for test-positive dogs. This cross-sectional study analyzed data obtained from IDEXX Laboratories, Inc. on 10,437 canine Leptospira PCR tests (blood and/or urine) submitted by Canada-based veterinarians (July 2009 to May 2018). Multivariable logistic regression was used to identify risk factors for test-positive dogs. Test-positive proportion varied widely annually (4.8–14.0%) and by location. Provinces with the highest test-positive proportion over the study period were Nova Scotia (18.5%) and Ontario (9.6%), with the prairie provinces (Manitoba and Alberta combined) having the lowest proportion (1.0%); the northern territories could not be evaluated due to limited testing. In the final model, dog age, sex, breed, month, and year test performed, and location (urban/rural, province) of the practice submitting the sample were significant predictors of a positive Leptospira PCR test. Dogs less than one year of age (OR = 2.1; 95% CI: 1.6–2.9), male sex (OR = 1.3; 1.1–1.5), toy breed (OR = 3.3; 2.5–4.4), and samples submitted from an urban practice (OR = 1.3; 1.0–1.8) had the greatest odds of a positive Leptospira PCR test as compared to referent groups. Significant two-way interactions between province-month and year-month highlight the complex spatial and temporal influences on leptospirosis occurrence in this region. Our work suggests a high incidence of canine leptospirosis regionally within Canada. Identifiable dog and location factors may assist in future targeted prevention efforts.